The Owl, the Dragon and the Magician: Reflections on Being an Anthropologist Studying Magic - Greenwood, Susan (The pomegranate, 2015)
This article documents the life of an anthropologist studying magic; it chronicles her trajectory of finding a place between the rationalized, analytically based academy on the one hand, and a life infused with spirits on the other. Not wanting to prioritize either critical thinking or the reality of a non-material world, Susan Greenwood shows how she has explored a magical terrain engaging sensory experiences, the imagination as a 'doorway' into an inspirited reality, and critical thinking through her anthropological work. Greenwood shows how she has negotiated often uncomfortable - but highly relevant - subjective and theoretical domains with the aim of not reducing or privileging one to the other. In the process she has sought to legitimize magic as an important aspect of knowledge that can bring academic - as well as individual - insights.